PELATIHAN SOFTWARE GEOGEBRA DAN SWISH MAX BAGI GURU MATEMATIKA KOTA AMBON - Tupamahu, Pieter Zakarias; Talakua, Marlyd; Mataheru, Wilmintjie (Universitas Pattimura, 2021)
The implementation of this community service aims to help teachers use technology as a learning medium during Face-to-Face Learning (PTM) and Distance Learning (PJJ) activities at junior high schools in Ambon City, where problems that often occur are related to improving teacher pedagogic competence. The object of this activity is all junior high school teachers of mathematics subjects in Ambon City. The learning process not only provides information from teachers to students, but learning must be prepared properly, one of which is through the provision of interesting learning media and by the times. Technology-based learning media solutions that can be used in the industrial era 4.0 are Geogebra Software and Swish Max, so that achievements in the learning implementation process can be obtained optimally. This training activity through community service (PkM) provides space for teachers to innovate in developing the quality of learning through the development of appropriate learning media